Constitutional Limits of Delegating Normative Authority to Non-State Bodies: The Case of Indonesia’s DSN-MUI - Hulwanullah, Hikam; Serfiyani, Cita Yustisia; Sari, Mieke Yustia Ayu Ratna; Yudisetyo, Zerry Akbar; Pratista, Farida Prima (Al-'Aqdu: Journal of Islamic Economics Law, 2025)
This study examines the constitutional limits of delegating normative authority to non-structural religious bodies in Indonesia, focusing on the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). As a private religious institution, DSN-MUI issues fatwas that are adopted by the Financial Services Authority, Bank Indonesia, and Sharia financial institutions as binding references in the regulation of Islamic finance. This delegation model raises fundamental constitutional questions regarding legality, accountability, and the distribution of power under the 1945 Constitution. Employing a normative legal method with statutory and conceptual approaches, the study finds that while DSN-MUI enjoys functional legitimacy in Sharia economic regulation, the absence of direct statutory basis and public oversight mechanisms poses risks to the principle of legality and checks and balances. The study recommends a co-regulation model where DSN-MUI fatwas must be formally adopted through state regulations and subject to transparent accountability mechanisms to ensure compliance with the rule of law and constitutional democracy.